Headache and vision changes in an elderly man with rheumatoid arthritis. (22nd May 2019) - Kwok, Timothy S.H.; Daneman, Nick; Lake, Shirley L.
Abstract: We present a case of an elderly, immunosuppressed patient with rheumatoid arthritis who was not appropriately vaccinated, and subsequently developed herpes zoster ophthalmicus, which initially presented similar to giant cell arteritis. Evidence‐based vaccinations are integral in decreasing the incidence of preventable diseases and promoting optimal health at the individual and population level. Although the patient ultimately did not suffer any long‐term adverse sequelae, this case highlights the importance of vaccination in the rheumatology setting, and to consider both inflammatory and infectious causes of headache and vision changes in the elderly.